Evaluation of Three Bridging Tricorticocancellous Bone Grafts in the Treatment of Old Non-uniting Fractured Humerus - Alkhuzai, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Nonunion of humeral shaft fracture after conservative treatments or frequent failed surgical treatment of bone healing exemplify the difficulties in managing a bone defect or severely damaged individuals. Aim of the study: The present study was undertaken to evaluate three bridging tricoticocancellous bone grafts in the treatment of old non-uniting fractured humerus. Materials and Methods: From June 2014 to December 2019, three bridging tricoticocancellous bone grafts were used to treat non-union humeral shaft fractures using dynamic compression plates at Sulaimani Teaching Hospital in Iraq. Results: Sixteen patients, 11 males, and 5 females, varying in age from 28 to 64 years old (mean age 41) were recruited for the study. Six patients had previously undergone conservative treatment, and ten patients had previously undergone surgical treatment, such as open reduction and internal fixation with plates and screws or various intramedullary nails. Four out of ten patients had previously received bone transplants in conjunction with internal fixation. The nonunion lasted between 2 and 4 years (a mean of 3 years). In patients who were treated by recanalization of the medullary canal healing rate of a non-uniting fractured shaft, humerus reached 100% in all 16 patients, indicating improvements in both bone healing and functional index outcomes. The satisfaction rate score was in 15 patients (93.75%). Also, the function score was excellent in 15 patients (93.75%), while the movement score was in 14 patients (87.5%). The union rate, angular deformity, and limb shortening were used to evaluate bone results. Conclusion: When using the technique of medullary recanalization opening the bone canal, and fixation by dynamic compression plate for old non-uniting fractured shaft humerus patients, the findings confirm that three bridging tricoticocancellous bone grafts are superior in healing and union, improved arm function, and a high satisfaction rate as achieved.